Dynamics, Silviculture and Management of Mixed Forests (Managing Forest Ecosystems,, 2018)
Concerns about the loss of biodiversity and the negative consequences for resilience have oriented management to adopt a diversification strategy. The interplays between environmental drivers, forestry alternatives and social demands from mixed forests have opened appealing research questions whose answers needed to be addressed: what species mixture is better adapted to current environmental conditions and social demands?, what species composition would cope better with climate change?, are mixtures always more productive than monocultures?, what are the drivers of stability in mixed stands?, how do ecosystem processes and functions in mixed forests affect the delivery of ecosystem services? This book provides some answers to these questions as a result of scientific and stakeholder exchange during meetings and scientific missions in the framework of the European Network on Mixed Forests (EuMIXFOR). The book is included in the Springer's book series Managing Forest Ecosystems in order to present state-of-the-art relating to mixed forests, their management, silviculture and dynamics in a cross-border context including examples from Europe, North Africa, and South-America. EuMIXFOR was funded by COST Action FP1206. COST (European Cooperation in Science and Technology) is a funding agency for research and innovation networks. Actions help connect research initiatives across Europe and enable scientists to grow their ideas by sharing them with their peers. This boosts their research, career and innovation. .